Coefficients of the Improved Global Pressure and Temperature (IGPT) model - Tao Li; Wang Lei (PANGAEA, 2019)
"P25para.dat","T25.para.dat" and "dpT25para.dat" include annual average, annual, semi-annual, diurnal, and semi-diurnal cycles parameters of global surface pressure, 2m temperature, and dew point temperature calculated from the ERA5 dataset from 2006 to 2015. "SurfaceElevation.dat" is the global surface elevation data. "EGMUndulation.dat" is used to convert the ellipoidal height to the orthometric height.